'Blundering Brutuses': Michael Field, Nonconformism, and The Politics of Social Purity. (17th September 2022) - Murray, Alex
Abstract: This article explores the contexts of nonconformism and social purity that underpin Michael Field's (Katharine Bradley and Edith Cooper) verse drama Brutus Ultor (1886). Based on new archival research, the article explores Bradley's role in the Ladies National Association for the Repeal of the Contagious Diseases Act and argues that the play is a complex commentary on the social purity movement and, in particular, on W.T. Stead's campaigning journalism. More broadly, the article argues for the importance of Michael Field's nonconformist background in the development of their oeuvre.